Meningkatkan Hasil Belajar Peserta Didik Melalui Model PBL di Kelas V Fase C SD Negeri 030436 Kerajaan - Marlin Pergaulan; Dicky Aprianto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research is aimed to improve student learning outcomes in the subjects of Catholic Religious Education and Character. In achieving the result of the research, the Problem Based Learning model was applied in the learning activities. The Problem Based Learning model is a learning model that presents a real problem for students as a starting point for learning and then resolved through investigation and applied by using a problem solving approach. This model provides the space for students to get involved actively. Through this active involvement, the students experienced the learning and showed their learning outcomes' improvement. This is shown from the results of research conducted in the 5th Grade Phase C students at SD Negeri 030436 Kerajaan. The Classroom Action Research carried out in two cycles, cycle I and cycle II, and showed positive results. The Learning outcomes in the P3 attitude and cognitive aspects got increased. The P3 attitude aspect in cycle I 77% as the average score became 84% in cycle II. Furthermore, the learning results of cognitive aspects 71.88 (cycle I) became 86.46 (cycle II). Hence, from these results, it can be concluded that the Problem Based Learning model can improve the learning outcomes of 5th Grade Phase C students at SD Negeri 030436 Kerajaan.